Predictive factors associated mortality after gastrectomy (Annals of Medical Research, 2021)
Aim: In this study, we aimed to identify the risk factors associated with postoperative mortality after gastrectomy.Surgical resection is the only potentially curative method for gastric cancer and is associated with severe morbidity and mortality. Material and Methods: Patients who underwent gastrectomy for gastric cancer in a single center between September 2015 and September 2018 were evaluated retrospectively. The relationship between postoperative mortality and clinical variables of the patients, tumor characteristics and 10 variables related to intraoperative characteristics were analyzed.Results: 133 patients were included in our study. Postoperative mortality occurred in 10 patients. Our postoperative mortality rate was 7.5%. Male sex (HR = 0.664, 95% CI =0.460–0.961, p=0.030), tumor localization (linitis plastica (HR = 3.594, 95% CI =1.375–9.390, p=0.009), tumor stage 3C (HR =1.713, 95% CI =0.906–3.239, p=0.0032) total gastrectomy (HR = 1.918 95% CI =1.042–3.532, p=0.036), conventional (open) surgery (HR = 2.807 95% CI =1.546–5.096, p= 0.001), operation duration >240 min (HR = 1.758, 95 % CI =1.064–2.906, p= 0.028), was independently associated with an increased risk of postoperative mortality. Age >60 (p=0.463), body mass index (p=0.414), ASA score >3 p=0.862, intraoperative blood loss >300 (p=0.083) and additional organ resection (p=0.649) were not independent risk factors for mortality.Conclusion: Anastomotic leakage was associated with male sex, obesity, and tumor localization. Anastomotic leakage is related with poor survival. Determining the risk factors after gastrectomy guides us in the management of patients at risk for postoperative mortality.
Keywords: Gastrectomy; complication; postoperaritive mortality